Peningkatan Proses dan Hasil Pembelajaran Bahasa Indonesia dengan Model Scramble Kelas III SDN 296/VI Rantau Panjang - Mayang Sari; Tri Wera Agrita; Elvima Nofrianni (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to improve the learning process and outcomes in the Indonesian language subject through the implementation of the Scramble learning model among third-grade students at SD Negeri 296/VI Rantau Panjang. The background of this research is based on initial findings indicating that most students had difficulty understanding the subject matter due to monotonous and less varied teaching methods. The research employed a Classroom Action Research (CAR) approach, which was conducted in two cycles. The instruments used included observation sheets for teacher and student activities, as well as learning outcome tests. The results showed a significant improvement in student engagement during the learning process and in academic achievement. Students’ learning activity improved from the “fair” category in the first cycle to “very good” in the second cycle. Furthermore, the percentage of student learning mastery increased to 80% in the second cycle. These findings demonstrate that the Scramble model is effective in creating an enjoyable and interactive learning environment, enhancing students’ understanding of the material more optimally.